Blockchain-enabled supply chain coordination for off-site construction using Bayesian theory for plan reliability - Kim, Minju; Zhao, Xianxiang; Kim, Yong Woo; Rhee, Byong Duk (Automation in Construction, 2023)
The potential of blockchain is being widely explored within the construction industry, particularly for transparent communication and information sharing. However, only limited research has focused on implementing blockchain to address the challenge of aligning conflicting interests among independent agents, specifically, supply chain coordination. This paper develops a blockchain-enabled supply chain coordination system that facilitates the alignment of diverse decisions made by stakeholders in an off-site construction supply chain. To achieve this goal, Bayesian updating is employed to estimate the probabilistic distribution of plan reliability, enabling the calculation of a supplier rebate that incentivizes the contractor to schedule deliveries aimed at minimizing joint supply chain costs. Additionally, the paper describes a blockchain-enabled system that allows practitioners to measure plan reliability. The research findings demonstrate that the blockchain-enabled supply chain coordination system fosters shared common knowledge among project stakeholders and facilitates real-time updates of changes in the contractor's plan reliability, aligning the interests of both the supplier and contractor.
Keywords: Bayesian theory; Bayesian updating; Block-chain; Coordination systems; Independent agents; Information sharing; Off-site construction; Plan reliability; Rebate pricing; Supply chain coordination; Bayesian updating; Blockchain; Off-site construction; Plan reliability; Rebate pricing; Smart contracts; Supply chain coordination